Reformatory Concepts of Educational and Care Activities in Regards to Neglected Children in the Kingdom of Poland at the Turn of the 19th and 20th Centuries in Comparison with European Solutions - Bołdyrew, Aneta (Biuletyn Historii Wychowania, 2018)
After the January Uprising in the Kingdom of Poland, across half of the following century, industrial development was mostly connected with social reforms. One tragic consequence of it was the increase in the number of children without parental protection, juvenile beggars, tramps, young criminals and prostitutes. During the last thirty years of the 19th century it became a priority in the Kingdom of Poland to pay attention to the education and protection of children and teenagers from the poorest families. Numerous innovative and educational concepts were formulated at that time; some of them were used in centres for socially maladjusted young people, for instance in Studzieniec, Mariańska Wilderness or Struga, in centres for young prostitutes. The activity of educational centres and societies which organised the protection of children (for example, The National Society for the Prevention of Cruelty to Children) was given as an example.